DISKRIMINASI DALAM NOVEL RUMAH KACA KARYA PRAMOEDYA ANANTA TOER - Ajopan, Depri; Hayati, Yenni; Nst., Muhammad Ismail (Universitas Negeri Padang, 2017)
This research is qualitative research using descriptive method. The data source is showing the form of discrimination, the causes of discrimination, and the impact of discrimination on the lives of characters. The technique of data collection through three stages, first read and understand the entire contents of the Glass House's novel works of Pramoedya Ananta Toer, the two mark each part of the novel that deals with discrimination, the three recorded data on the forms and causes of discrimination using the format of the inventory data. Based on the results of data analysis that has been done against Greenhouse novel works of Pramoedya Ananta Toer, three forms of discrimination can be summed up as follows: (1) racial discrimination, (2) gender discrimination, and (3) discrimination elite. Two causes of discrimination are reflected in the novel, namely: (1) the difference in the group, and (2) social identity. The impact of discrimination for the life of the characters in the novel, including (1) bring up the hostility between groups, (2) the occurrence of killings, and (3) give birth to poverty.Keywords: Discrimination, Rumah Kaca, Racial Discrimination